MORPHOLOGY AND MORPHOMETRY OF Haemonchus contortus IN GOATS IN YOGYAKARTA, INDONESIA - Priyo Sambodo; Joko Prastowo; Sudarmanto Indarjulianto; Kurniasih Kurniasih (Jurnal Kedokteran Hewan, 2018)
This research was carried out to determine the morphology and morphometry of Haemonchus contortus in goats. Adult female parasites were collected from abomasum of naturally infected goats and stored in lactophenol. Images of the parasite were acquired using lucida camera and measurement was performed using Axiovision LE software. Basic characters of the morphology and morphometry of Haemonchus spp. were identified by determining the value of the discriminant function of three parameters on spicule. Vulvar morphology was identified by vulvar flap shape. Data were presented in terms of mean, standard deviation, and percentage. A hundred percent of the parasites were H. contortus with discriminant function value 0.63. The size of female parasites was longer and wider (25.5-32.6 mm; 0.38-0.63 mm) than that of male ones (17.3-20.0 mm; 0.24-0.33 mm). There were only 2 varieties of vulvar flap, linguiform (81%), and knobbed (19%). There were 5 subclasses identified in the linguiform type, including linguiform A (39%), linguiform B (22%), linguiform C (17%), linguiform I (1%), and a new subclass of linguiform D (2%). Based on the the type of vulvar flap, H. contortus found in goats in Yogyakarta were different to those found in previous researches. The findings could be used in identifying the parasite species in small ruminants.